Evaluation of Standardization and Antiglycation Activity of Leaf Part of Barleria Prionitis L. - Utami, Nastiti; Amin, Muhammad Saiful; Angelia, Putu Tia; Paramesti, Nathania Anindya (Indonesian Journal of Global Health Research, 2024)
The number of deaths due to stroke among diabetic patients escalated from 52,397 to 114,092. Similarly, fatalities from ischemic heart disease (IHD) in individuals with diabetes rose from 35,351 to 76,974, while deaths from chronic kidney disease in this population increased from 29,061 to 63,279. Overall, the mortality rate attributable to diabetes and its complications surged by 117% over a span of 25 years, averaging an annual increase of 4.7%. Increased glucose concentrations produce advanced glycation end products (AGEs). The reactions associated with protein glycation that lead to an overproduction of AGEs are primarily responsible for a range of complications related to diabetes. The potential of alternative medicine derived from plants can be explored. Phytochemicals found in Barleria species include iridoids, kaempferol, ferulic acid, and caffeic acid. Barleria prionitis L., a plant of medicinal significance, is classified within the Acanthaceae family. Objective: The study investigated standardization and antiglycation activity of crude dry extract of Barleria prionitis L. Method: The principle of antiglycation is the inhibition of the reaction of the formation of AGEs which the products of the glycation reaction between protein and glucose, and are measured using a UV-vis spectrophotometer. Result: The results of the standardization indicate that EEBL has a water soluble compound content of 40.45 ± 0.56%, an ethanol soluble compound content of 15.08 ± 0.74%. This is indicated the amount of compounds that dissolve in water compared to ethanol. The number of dissolved compounds reflects the quantity of secondary metabolite compounds that have been solubilized in the solvent. A water content of 7.508 ± 0.399%, a total ash content of 9.41 ± 0.67%, an acid insoluble ash content of 2.17 ± 0.03%, and an extract density of 0.913 ± 0.015 g/mL. Additionally, EEBL was found to contain flavonoids, alkaloids, tannins, saponins, and triterpenoids. Antiglycation activity results obtained IC50 values of 177.02 ± 0.80 mg/L. EEBL contains secondary metabolite compounds such as flavonoids, phenolics, and terpenes, that can act as free radical scavengers. The mechanism of polyphenol antioxidant protection is associated with its ability to bind proteins, thereby preventing the formation of AGE. Conclusions: This study provides the results of the antiglycation activity of standardized EEBL. These findings offer valuable insights for further investigation of the in vivo antidiabetic properties, as well as data that may contribute to the development of new herbal medicines and dietary supplement formulations utilizing the crude extract.